2022
DOI: 10.1080/25726668.2022.2082152
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of failure associated with longwall face during the main weighting period using a numerical modelling approach

Abstract: A FLAC 3D based model has been developed to estimate the extent of coal wall spalling for a longwall face having a working depth of 406.5 m during the main weighting period. The results obtained from the model helped in characterizing two key phases of main weighting, namely, peak stress, and main fall period based on vertical stress concentration factor, percentage of yield zones, and extent of yielding ahead of the face. The maximum extent of coal wall spalling of 2 m was observed during the main fall period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Figure 12 shows the validation of the yield zone observed in this study with the published literature. From this Figure, it can be understood that the maximum of 5 m yield zone occurred in 23 and that of 2 m minimum occurred in 18 . It is also reported that the 79.4% of face falls extended less than 1 m, 20% lies between 1 and 2 m, 0.6% lies beyond 2 m at longwall face (Face # 1306, at a depth of 637 m) of Zhaozhuang coal mine in China.…”
Section: Validation Of the Yield Zone Observed In The Numerical Analysismentioning
confidence: 78%
See 2 more Smart Citations
“…Figure 12 shows the validation of the yield zone observed in this study with the published literature. From this Figure, it can be understood that the maximum of 5 m yield zone occurred in 23 and that of 2 m minimum occurred in 18 . It is also reported that the 79.4% of face falls extended less than 1 m, 20% lies between 1 and 2 m, 0.6% lies beyond 2 m at longwall face (Face # 1306, at a depth of 637 m) of Zhaozhuang coal mine in China.…”
Section: Validation Of the Yield Zone Observed In The Numerical Analysismentioning
confidence: 78%
“…Very few studies 17 20 , 23 were undertaken to estimate the yield zone in the longwall face, floor and immediate roof. Figure 12 shows the validation of the yield zone observed in this study with the published literature.…”
Section: Validation Of the Yield Zone Observed In The Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…3) applying the boundary condition and in situ stress; and 4) solving the model to find an equilibrium state so that excavation can start [25].…”
Section: Numerical Model Creationmentioning
confidence: 99%